2016
DOI: 10.1016/j.ygyno.2016.04.001
|View full text |Cite|
|
Sign up to set email alerts
|

Sequencing of mutational hotspots in cancer-related genes in small cell neuroendocrine cervical cancer

Abstract: Objectives Small cell cervical cancer is a rare malignancy with limited treatment options for recurrent disease. We sought to determine if tumor specimens of small cell cervical cancer harbor common somatic mutations and if any of these are actionable. Methods Using a registry of patients with neuroendocrine cervical cancer, we identified 44 patients with pure or mixed small cell cervical cancer who had undergone mutational analysis. Mutations had been detected using next generation sequencing of mutational … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
58
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(69 citation statements)
references
References 28 publications
9
58
2
Order By: Relevance
“…29 Similarly, mutations in PIK3CA, one of the most frequently mutated genes in HPV-related cancers, were detected in 18% (eight of 44) of SmCC-Cx in a hotspot-based study. 30 In contrast, a study using whole exome sequencing identified recurrent mutations in five cases of SmCC-Cx, including ATRX, ERBB4 and AKT/mTOR pathway genes NF1, PTEN, RICTOR and TSC1/2, which is akin to neuroendocrine tumours arising in sites unrelated to HPV infection. 31 These emerging data have the potential to unveil targets for therapy which, in conjunction with immune modulation treatments, may change the course of the disease.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…29 Similarly, mutations in PIK3CA, one of the most frequently mutated genes in HPV-related cancers, were detected in 18% (eight of 44) of SmCC-Cx in a hotspot-based study. 30 In contrast, a study using whole exome sequencing identified recurrent mutations in five cases of SmCC-Cx, including ATRX, ERBB4 and AKT/mTOR pathway genes NF1, PTEN, RICTOR and TSC1/2, which is akin to neuroendocrine tumours arising in sites unrelated to HPV infection. 31 These emerging data have the potential to unveil targets for therapy which, in conjunction with immune modulation treatments, may change the course of the disease.…”
Section: Discussionmentioning
confidence: 97%
“…A recent study using targeted next‐generation gene sequencing on 10 patients with SmCC‐Cx identified recurrent somatic mutations involving the MAPK , PI3K/AKT/mTOR and TP53/BRCA pathways . Similarly, mutations in PIK3CA , one of the most frequently mutated genes in HPV‐related cancers, were detected in 18% (eight of 44) of SmCC‐Cx in a hot‐spot‐based study . In contrast, a study using whole exome sequencing identified recurrent mutations in five cases of SmCC‐Cx, including ATRX , ERBB4 and AKT/mTOR pathway genes NF1 , PTEN , RICTOR and TSC1/2 , which is akin to neuroendocrine tumours arising in sites unrelated to HPV infection .…”
Section: Discussionmentioning
confidence: 99%
“…Frumovitz et al 29 identified 44 patients with pure or mixed small-cell cervical cancer. All patients underwent mutational analysis using next-generation sequencing of mutational hotspots in 50 cancer-related genes.…”
Section: Molecular and Immune Profile Testingmentioning
confidence: 99%
“…We found that 48% of patients with small cell cervix cancer had a druggable mutation; these included mutations in PIK3CA (18%), KRAS (14%), and TP53 (11%). [19] On the basis of molecular testing, one patient had a KRAS mutation identified in her tumor and was treated with a MEK inhibitor, and this patient achieved a complete response. [20]…”
Section: Discussionmentioning
confidence: 99%